Nutritional therapy in prolonging the period of remission in patients with Crohn's disease: a systematic review of the literature (Research, Society and Development, 2022)
Crohn's disease (DC) is a chronic inflammatory disease of unknown origin that causes injuries segmental and asymmetrical from the mouth to the anus. The prevalence of DC is increasing in the world in adults and children, and therefore this study seeks nutritional therapies that improve the quality of life of these patients, and decrease the symptoms of diarrhea, abdominal pain, rectal bleeding, fever, weight loss and fatigue. Objective: to analyze the effectiveness of nutritional interventions for the treatment and prolongation of low symptoms of Crohn's Disease. Methodology: this is a systematic literature review, searches in the Virtual Health Library (VHL) and National Library of Medicine (PubMed) databases. Original studies were selected, without language or temporality delimitations, taking into account the research question. Results and Discussion: In the studies examined, dietary treatments obtained efficacy data from the literature for Exclusive Enteral Nutrition (SEN) in children newly diagnosed with DC regardless of age, induces subclinical in the first outbreak or during relapses, induces mucosal healing and bowel wall, has a positive effect on bone structure, associated with improved nutritional status and disease stage. Final considerations: the studies revealed significant evidence with Nutrition, from dietary manipulation to Enteral Nutrition (EN), that play an essential role in the treatment of DC.